Perceptions of the coach-athlete relationship predict the attainment of mastery achievement goals six months later: A two-wave longitudinal study among F. A. Premier League Academy soccer players - Nicholls, A. R.; Earle, K.; Earle, F.; Madigan, D. J. (Frontiers in Psychology, 2017)
All football teams that compete within the F. A. Premier League possess an academy, whose objective is to produce more and better home-grown players that are capable of playing professionally. These young players spend a large amount of time with their coach, but little is known about player`s perception of the coach-athlete relationship within F. A. Premier League Academies. The objectives of this study were to examine whether perceptions of the coach-athlete relationship changed over six months and if the coach-athlete relationship predicted self-reported goal achievement among F. A. Premier League academy players. This study included cross-sectional (n = 104) and longitudinal (n = 52) assessments, in which academy soccer players completed a measure of the coach-athlete relationship and goal achievement across either one or two time periods. The cross-sectional data were subjected to bivariate correlations, whereas the longitudinal data were analyzed using multiple regressions. Perceptions of the coach-athlete relationship remained stable over time. The coach-athlete relationship predicted the achievement of mastery goals six months later. Enhancing the quality of the coach-athlete relationship among elite adolescent athletes appears to be a suitable way of maximizing mastery achievement goals, particularly among developmental athletes who participate in team sports.